Students' Mathematical Literacy Ability In Solving High Order Thinking Skills Problems of Class XI Linear Program - Kusumadewi, Oriza; Khotimah, Rita Pramujiyanti (Universitas Wiralodra, 2025)
The development of mathematical literacy is a critical aspect of mathematics education in Indonesia. Beyond computational proficiency, students must be equipped to apply mathematical concepts in real-life problem-solving scenarios. This study focuses on analyzing the mathematical literacy skills of grade XI students at SMA Negeri 2 Blora in solving Higher Order Thinking Skills (HOTS) problems related to linear programming. Employing a descriptive qualitative method, the research involved three participants representing high, medium, and low literacy proficiency levels. Data collection was conducted through written assessments and interviews, and data validation was ensured using triangulation techniques. Data analysis followed steps of collection, reduction, presentation, and conclusion drawing. The findings reveal that students with high literacy proficiency demonstrated competency across all mathematical literacy indicators, including communication, the use of language and operations, symbols, formal and technical aspects, mathematization, representation, problem-solving strategies, and reasoning. Meanwhile, students with moderate proficiency fulfilled only some indicators, specifically communication and the application of language and operations. In contrast, students with low proficiency exhibited mastery solely in communication.